ASSA13-17-3 The Prospective Clinical Trial of Intensive Insulin Therapy in the Control of Perioperative Hyperglycemia For the Children Undergoing the Palliative Congenital Heart Surgeries. (29th April 2013) - Hong, Liang; Wang, Xu; Chen, Qiuming; Liu, Fangchao; Zhang, Yanbo; Yang, Juxian; Duan, Leilei; Zeng, Min; Li, Shengli; Chen, Zerui; Jia, Yan; Li, Shoujun
Abstract : Objective: The intensive insulin therapy (IIT) has shown great results in the therapy of acquired cardiac lesions' surgeries during intensive care unit (ICU) while it's unknown in the palliative operations for complex congenital heart disease (CHD). This trial was to estimate the results for controlling the hyperglycemic in the palliative heart surgeries in CHD children during the paediatric intensive care unit (PICU) stays. Methods: We enrolled 79 children diagnosed with congenital complex cardiac lesions who are going through the palliative operations. They were assigned into two groups randomly by computer, the IIT (n = 39) and conventional insulin therapy (CIT) group, which blood glucose concentrations ranges were 70–130 mg/dL and 70–220 mg/dL, respectively. The insulin infusion is pumped continuously to the children once glycemic level exceeds the upper limit of their own group after the surgeries back to PICU. In this prospective clinical trial we consider the hypoglycemic as the blood glucose falls below 70mg/dL and the 50% dextrose solution will be given to deal with the hypoglycemia till the glycemic is back into the settled range of their own group with the double check of blood glucose concentration. The PICU stays, chest effusion, transfusion, blood tests and major complications were documented to analysis. Results: There was no hospital death and two infants in CIT group received the secondary surgeries for post-operation bleeding. One neonate and an infant in IIT group were excluded from this study due to the cardiopulmonary resuscitation for pulmonary hypertension crisis and the use of extracorporeal membrane oxygenation (ECMO) for low cardiac output syndrome. The incidence of hypoglycemia in IIT group was 19% while the one in CIT group was 11% (p = 0.047). The mean peak blood glycemic in IIT and CIT was 161 mg/dL and 221 mg/dL, respectively, which showed significant statistical differences (p = 0.013). The mean PICU stays and ventilation hours in both groups were no significant difference. The mean chest effusion in CIT group was 312 mL in the children of Fontan circulation, which was much less than that of IIT group (p = 0.031). The total hospital days in two groups were no statistical differences (p = 0.057). Conclusions: The children in IIT group got better short outcomes than that of CIT group. It's important to enlarge the population in this trial and other complex CHD would be included to analysis to acquire more information on the controlling of hyperglycemia in the perioperative care for complex CHD children.